Penatalaksanaan HIV dalam Kehamilan - Sintong Halomoan Sianturi (Universitas Katolik Widya Karya Malang, 2023)
HIV infection has been a global epidemic around the world. in the absence of intervention, the rates of HIV transmission during pregnancy, labor or breastfeeding vary from 15-45%. Data from Indonesia Health ministry 2011 shows 21.103 pregnancy women who undergone HIV test 534 (2,5%) are positive HIV infected. The use of antiretroviral (ARV) drugs has been success prevent mother to child transmission. Zidovudine monotherapy shows transmission rates (4,8%) higher than ARV combination. ARV combination that can use during pregnancy vary from triple NRTI, 2 NRTI + NNRTI, or 2 NRTI + PI with similar high virological supression rates. it has beeen shows a changing trend from sectio caesar to vaginal delivery with decrease of viral load using ARV combination, with increase percentage for vaginal delivery from 17% to 52%. Women who receive >9 weeks pre partum prophylaxis significantly have undetectable viral load in plasma and breast milk during labor.